Influence of simulation in Malaysian healthcare education and research (ISIM-HERE): a two-decade experience - Ismail Mohd Saiboon; Johar MI; Siraj HH; Arif K; Jalina K; Iva MI; Saidah MH; Balakrishnian M; Syahira J; Phrampus PE (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
The use of simulation as a teaching methodology in medical institutions has been in Malaysia for over two decades. This study aimed to evaluate the current scenarios of simulation impact and utilization in Malaysian academic healthcare institutions (AHIs). We conducted a population-based survey on all AHIs in Malaysia including public and private. We performed an online survey followed by a face-to-face interview evaluating the number of institutions that used simulation, duration of experience, purpose, funding, users’ category and healthcare domain, research activities, dedicated-trained staff and the challenges faced. Out of 75 healthcare institutions approached, 38 agreed to participate in this study. Twenty-two (57.9%) were public hospitals while 16 (42.1%) were private institutions. Thirty-five (92.1%) out of 38 institutions used simulation as a teaching method. The majority (15, 42.9%) had less than five years’ experience, and about a third (11, 31.4%) used simulation for teaching, training and performance assessment. Nurses (30, 26.1%) were the main users followed by physicians and paramedic (19, 16.5% each respectively). In-hospital and procedural group were the top two domains of utilizers. Almost three quarters (25, 71.4%) have dedicated support staff to manage the centre. Funding was mainly from internal institutional support mechanisms. Seven different categories of challenges were identified, the biggest being financial support. In summary, even though healthcare simulation has been in Malaysia for the past two decades but the most substantial impact happened over the last five years. Utilization was mainly for teaching, training, and performance assessment with minimal use in research.